Um estudo sobre os modelos operacionais dos bancos centrais autônomos no mundo - Forjaz, Luiz Henrique Petersen (2007)
The bill of the Senate of no. 317 of 2003, that establishes the operational autonomy of the Central Bank of Brazil, is a great step towards an institutional modernization of the country. Being that approved autonomy, a crucial subject that proceed is how the institutional drawing of the Central Bank of Brazil will be. Which areas will be linked to BACEN and which areas will be out? Who will determine the goal? Who will be the members of COPOM? Those are just some subjects that appear when it is spoken in autonomy of the central bank. Several examples of autonomous central banks exist in the world and that study will analyze how those central banks operate, so that hereafter we can try to draw an institutional arrangement that adapts to the Brazilian needs.